PENGARUH SUPPORTIVE WORK ENVIRONMENT, WORK LIFE BALANCE DAN SERVANT LEADERSHIP TERHADAP RETENSI KARYAWAN DI LEMONDIAL GROUP - Silvina Claudia Mbio; Fransiscus Amonio Halawa (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to examine the effect of Supportive Work Environment, Work Life Balance, and Servant Leadership on Employee Retention at LeMondial Group. This research employed a quantitative approach with an associative method. A saturated sampling technique was used, involving all 39 permanent employees as respondents. Data were collected through questionnaires and analyzed using multiple linear regression with IBM SPSS version 25.The results indicate that Supportive Work Environment and Work Life Balance have a positive and significant effect on Employee Retention. Meanwhile, Servant Leadership does not have a significant effect on Employee Retention. Simultaneously, Supportive Work Environment, Work Life Balance, and Servant Leadership have a significant effect on Employee Retention. The Adjusted R Square value of 0.479 indicates that 47.9% of the variation in Employee Retention can be explained by these variables, while the remaining 52.1% is influenced by other factors outside this study. The findings confirm that efforts to improve Employee Retention at LeMondial Group are more strongly influenced by the creation of a supportive work environment and the maintenance of a balance between employees’ work and personal lives. Therefore, the company is encouraged to maintain a supportive work environment and promote Work Life Balance as an effort to enhance Employee Retention.